A new tool path for optical freeform surface fast tool servo diamond turning. (December 2014) - Liu, Qiang; Zhou, Xiaoqin; Xu, Pengzi
Fast tool servo–assisted ultra-precision diamond turning has been extensively regarded to be a very promising technology for the fabrication of optical freeform surfaces, and micro- and nano-structured surfaces with high efficiency and high surface quality. This article describes a changing feed-rate tool path which can adjust the tool position arbitrarily both in the x-direction and z-direction to obtain homogenous surfaces. Meanwhile, it can improve machining efficiency, save cutting parameters calculation time, and avoid over-cutting at workpiece center. Cutting experiment is carried out to implement the new tool path.